2022
DOI: 10.1186/s12934-022-01758-9
|View full text |Cite
|
Sign up to set email alerts
|

Mucor circinelloides: a model organism for oleaginous fungi and its potential applications in bioactive lipid production

Abstract: Microbial oils have gained massive attention because of their significant role in industrial applications. Currently plants and animals are the chief sources of medically and nutritionally important fatty acids. However, the ever-increasing global demand for polyunsaturated fatty acids (PUFAs) cannot be met by the existing sources. Therefore microbes, especially fungi, represent an important alternative source of microbial oils being investigated. Mucor circinelloides—an oleaginous filamentous fungus, came to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 180 publications
(199 reference statements)
0
17
0
1
Order By: Relevance
“…Thus, GLA production by oleaginous microorganisms is a promising alternative to plant-based production. Mucor circinelloides , an oleaginous fungus, has been broadly employed to study GLA production, and it has been chosen as a model oleaginous microbe to produce GLA in various studies ( 7 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, GLA production by oleaginous microorganisms is a promising alternative to plant-based production. Mucor circinelloides , an oleaginous fungus, has been broadly employed to study GLA production, and it has been chosen as a model oleaginous microbe to produce GLA in various studies ( 7 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The term single cell oils (SCOs), also named microbial lipids or microbial oils, was created by Ratledge & Wynn since 1974, to identify those lipids of single-cell organismsmicroorganismsthat would be suitable for consumption by human and animal (Ratledge, 2004). Thus, they are considered as new sources of nutraceuticals, cosmeceuticals (products applied topically) or nutricosmetics (products that are ingested orally) of great value for human use (Hyde, et al, 2010;Béligon, et al, 2016;Galán, et al, 2020;Kothri, et al, 2020;Shah, et al, 2021;Fazili, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, fatty acids commonly found in cosmetics can be produced by fungi (Ward & Singh, 2005;Hyde, et al, 2010). Filamentous fungi of Mucorales and Mortieralles orders, such as Mortierella sp., Mortierella alpina, Umbelopsis isabellina, Cunninghamella echinulata, Mucor circinelloides and M. hiemalis, are more intensively studied for the production of essential fatty acids (Li, et al, 2015;Zhao, et al, 2015;Kosa, et al, 2018;Kikukawa, et al, 2018;Fazili, 2022). These microorganisms produce desaturases by introducing multiple double bonds into the esterified acyl chains at the beta position in membrane lipids (Bellou, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicated that the production of microbial oils by bacteria, yeasts and fungi becomes, in fact, an ecological and economically viable alternative, which can replace biodiesel, since these microorganisms can reach high levels of lipids, regardless of the climate, seasonality and high labor costs (Montero-Rodríguez, et al, 2016;Dvoretsky, et al, 2018;Carmona-Cabello, et al, 2021). Several microorganisms have the ability to accumulate more than 20% of lipids in their dry weight, and this value can reach up to 70% during the period of metabolic stress (Bao, et al, 2021;Fazili, et al, 2022). They are commonly called oleaginous microorganisms or single cell oils (SCOs), and have an important role in replacing vegetable biodiesel (Berikten & Hoşgün, 2022).…”
Section: Introductionmentioning
confidence: 99%